Changing trends in antibiotic resistance for urinary E. coli infections over five years in a university hospital. (March 2014) - Teoh, Penelope; Basarab, Adriana; Pickering, Ruth; Ali, Ahmed; Hayes, Matthew; Somani, Bhaskar K
Objective: We wanted to look at the antibiotic resistance patterns in our university teaching hospital for E. coli cultured from urine to assess the resistance profiles to common antibiotics used in the hospital. Patients and methods: Results were obtained of all positive urine cultures between January 2007 and December 2011 both from the hospital and urology department. Trends in susceptibility and resistance data for E. coli to trimethoprim, amoxicillin, ciprofloxacin, gentamicin and nitrofurantoin were examined. Results: A total of 40, 722 hospital urine specimens were culture positive in the five-year period, of which 15, 311 (37.6%) grew E. coli. Across the hospital there was no evidence of change in resistance to trimethoprim over the five-year period (38.1% in 2007 compared to 36.6% in 2011; p = 0.313). The percentage resistance to amoxicillin rose slightly (52.6% to 54.4%), and this was statistically significant (p = 0.011). Overall there was a statistically significant fall in resistance to ciprofloxacin but resistance has remained stable for the last three years (15.5% to 13.5%, p = 0.013). A trend of increasing resistance to gentamicin (p = 0.002) resulted from the 2007 baseline of 3.4% to 4.9% in 2008, but resistance remained stably low thereafter. Resistance to nitrofurantoin fell significantly (from 10.4% to 1.6%; p ≤ 0.0005). Conclusions: The number of E. coli-positive urine cultures from hospital in-patients remained broadly stable over this five-year period. Resistance to trimethoprim and amoxicillin remains high. Gentamicin resistance remains low, but the statistically significant rise over the five-year period suggests resistance rates should continue to be carefully monitored. Nitrofurantoin resistance is very low and has significantly decreased. This narrow-spectrum antibiotic should be considered the mainstay for treating uncomplicated urinary tract infections in females.